Kerjasama Pemerintah Desa Dalam Mensukseskan Program Keluarga Berencana Di Desa Sebemban Kecamatan Muara Wis Kabupaten Kutai Kartanegara - Herlina Eka Astuti; Adam Idris; Melati Dama (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This research aims to find out and describe village government cooperation in making the family planning program a success in Sebemban Village, Muara Wis District, Kutai Kartanegara Regency, as well as to identify the inhibiting factors. This type of research uses a qualitative descriptive method, with a research focus, namely facilitators and planners as well as inhibiting factors in Village Government collaboration in the succes of family planning programs in Sebemban Village, Muara Wis District, Kutai Kartanegara Regency. In this study the key informants were the Head of Welfare and Community Services, Village Government Staff, Head of the Empowerment and Family Welfare Mobilization Team, Members of the PKK Mobilization Team, and other informants, namely the community. The collection techniques used were observation, interviews and documentation. The data analysis used is an interactive model developed by Miles, Huberman and Saldana. However, the existence of obstacles in these efforts can help policy implementers to find out deficiencies and what needs to be improved in cooperation to make the family planning program successful in Sebemban Village, Muara Wis District, Kutai Kartanegara Regency.